Vai trò trợ tương hợp của TH1 có khối lượng phân tử phù hợp với một số hệ blend trên cơ sở cao su thiên nhiên - Thế, Ngô Kế; Kháng, Đỗ Quang; Diệu, Trần Vĩnh (Vietnam Journal of Chemistry, 2014)
Thanks to the structure properties, liquid natural rubber (LNR) was used by several authors as compatibilizer for polymer blends based on the natural rubber. This paper gave an overview about the influence of the compatibilizer TH1 – LNR with the end OH-groups on the morphology and properties of the research blend systems. The research results showed that TH1 with the molecular weight of 8.500 had the best compatible effect for the blends NR/PE, NR/SBR and NR/NBR. This compatibilizer TH1 was good for the blends the components of which had the little polarity difference like NR/SBR. The phase morphology showed a good component dispersion. The mechanical and technical properties of the polymer blends were significantly improved by using this compatibilizer